Ice Streams of the Laurentide Ice Sheet - Winsborrow, Monica; Clark, Chris; Stokes, Chris (Géographie physique et Quaternaire, 2004)
AbstractIce streams had a major influence on the configuration and the stability of the Laurentide Ice Sheet. Their identification is crucial for an understanding of ice sheet behaviour and their importance is reflected by the recent increase in paleo-ice stream research. This paper provides a synopsis of Laurentide paleo-ice streams, compiled from published sources and our mapping from satellite imagery and aerial photography. In total, 49 hypothesised ice streams are reviewed, and categorised according to the strength of evidence for streaming and knowledge of their extent. A map of Laurentide paleo-ice streams is presented, along with tables documenting the nature of evidence on which streaming behaviour has been invoked. The distribution of ice streams demonstrates the spatial organisation of fast ice flow, and overlapping imprints document major changes in ice flow during retreat. We note that Laurentide paleo-ice streams exhibit a much greater range in size than those currently operating in Antarctica.